2021
DOI: 10.1126/sciadv.abk1117
|View full text |Cite
|
Sign up to set email alerts
|

Observation of bound states in the continuum embedded in symmetry bandgaps

Abstract: Designing the photonic environment yields a mechanism for creating bound states in the continuum over a wide range of angles.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…For a metasurface state to be a symmetry-protected BIC (regardless of whether the state is degenerate), the state must be at the center of the Brillouin zone, k ∥ = Γ , and be even with respect to 180° rotation about the out-of-plane axis ( C 2 ) or be at a momentum-space polarization singularity 57 , 58 . The first requirement can be proven as a consequence of the Bragg-diffraction limit and the degeneracy between s- and p-polarized waves in free space 59 , while the latter requirement stems from the fact that the radiative channels at Γ in free space (or any homogeneous and isotropic environment) are always odd with respect to C 2 . In particular, this latter requirement is especially restrictive for symmetry-guaranteed degenerate states, as even though there are a few different possibilities of the metasurface’s in-plane rotational symmetry that allow for symmetry-guaranteed degeneracies, only the presence of six-fold rotational symmetry ( C 6 ) allows for degenerate pairs that are simultaneously even with respect to C 2 (these states form the E 2 irreducible representation regardless of whether reflection or time-reversal symmetry has been added to the system).…”
Section: Resultsmentioning
confidence: 99%
“…For a metasurface state to be a symmetry-protected BIC (regardless of whether the state is degenerate), the state must be at the center of the Brillouin zone, k ∥ = Γ , and be even with respect to 180° rotation about the out-of-plane axis ( C 2 ) or be at a momentum-space polarization singularity 57 , 58 . The first requirement can be proven as a consequence of the Bragg-diffraction limit and the degeneracy between s- and p-polarized waves in free space 59 , while the latter requirement stems from the fact that the radiative channels at Γ in free space (or any homogeneous and isotropic environment) are always odd with respect to C 2 . In particular, this latter requirement is especially restrictive for symmetry-guaranteed degenerate states, as even though there are a few different possibilities of the metasurface’s in-plane rotational symmetry that allow for symmetry-guaranteed degeneracies, only the presence of six-fold rotational symmetry ( C 6 ) allows for degenerate pairs that are simultaneously even with respect to C 2 (these states form the E 2 irreducible representation regardless of whether reflection or time-reversal symmetry has been added to the system).…”
Section: Resultsmentioning
confidence: 99%
“…However, as the periodicity is in the normal direction, the scintillation light is not expected to be well out-coupled with the radiation channels, because of the k z = 0 requirement of the quasi-BIC (confinement is at the Γ point). A better strategy for realizing BIC enhancement in the structure with cm thickness is exploiting the three-dimensional (3D) nanostructures [46], such as with the woodpile architecture [40] (Figure 7). Although, the fabrication of such structures is more challenging than simple 1D or 2D designs, it has been recently shown that they can provide a good platform for BIC type effects.…”
Section: Discussionmentioning
confidence: 99%
“…Some new attempts to engineer the radiation environment to achieve so-called lines of BICs have emerged quite recently [14]. But the idea and reported results require very complicated geometries [15], which are challenging to fabricate.…”
Section: Introductionmentioning
confidence: 99%